Front side illuminated dye-sensitized solar cells using anodic TiO2 mesoporous layers grown on FTO-glass - Lee, Kiyoung; Kim, Dam-Hee; Berger, Stefan; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2012)
In the present work, we investigate the performance of anodic, self-organized TiO2 mesoporous structures (TMSs) in dye-sensitized solar cells (DSSCs) under front-side illumination conditions. In order to fabricate structures usable in a front-side (FS) configuration, TMSs were formed on FTO glass by a full anodic conversion of evaporated Ti films on the glass substrate in a glycerol/K2HPO4 electrolyte at 180 °C. The resulting mesoporous layers can be assembled to FS dye sensitized solar cells which show a thickness of only 3 extgreekmm and a remarkable efficiency of 4.34%. This is significantly higher than, for example, anodic TiO2 nanotubes of the same length even after efficiency enhancing TiCl4 treatments (3.01%). The best efficiency value for TMS-based DSSCs that we currently reached is for a 7 extgreekmm thick TMS layer, this is ≈6.82% which is highly promising for further improvements.
EAM Import::2019-03-14